2018
DOI: 10.30821/jcims.v2i1.1738
|View full text |Cite
|
Sign up to set email alerts
|

SYEKH ABDUL HALIM HASAN, 1901-1969: Akar Tradisi Intelektual di Sumatera Timur Awal Abad XX

Abstract: <strong>Abstrak: </strong>Penelitian ini mengkaji biografi dan kiprah intelektual Syekh Abdul Halim Hasan di Sumatera Timur. Keberlangsungan tradisi intelektual di Sumatera Timur dipengaruhi, salah satunya, oleh kemunculan ulama-ulama di kawasan ini. Sebagian mereka berasal dari etnis Melayu, dan tidak sedikit dari mereka merupakan ulama yang berasal dari etnis Mandailing yang merantau dari kawasan Tapanuli ke Sumatera Timur. Studi ini mengkaji bagaimana peran Syekh Abdul Halim Hasan yang berasal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…The in-depth study of the Tapanuli ulama has very limited, there are only a few studies, including studies on Abdurrahman Sjihab: 1910-1955 [4], Syekh Abdul Halim Hasan: 1901-1969 [5], Syekh Ali Hasan Ahmad al-Dary [6] [7]. There are also the study about Islam in Tapanuli which talks about ulama and tarekat [8].…”
Section: Pvj-ishessh 2021mentioning
confidence: 99%
“…The in-depth study of the Tapanuli ulama has very limited, there are only a few studies, including studies on Abdurrahman Sjihab: 1910-1955 [4], Syekh Abdul Halim Hasan: 1901-1969 [5], Syekh Ali Hasan Ahmad al-Dary [6] [7]. There are also the study about Islam in Tapanuli which talks about ulama and tarekat [8].…”
Section: Pvj-ishessh 2021mentioning
confidence: 99%
“…In this case not only religious knowledge, but also must study general sciences. 62 Despite the fact that the percentage of Zainal Arifin Abbas is more inclined to the religious sciences as written in many works. At least, his study of the press sciences, journalism, and politics until English language has shown that he is not antigeneral sciences.…”
Section: The Classification Of Sciencesmentioning
confidence: 99%
“…Artikel ini secara khusus membahas tentang tradisi menulis yang berkembang dalam konteks peradaban Islam Melayu, namun belum menyentuh secara detail terkait tradisi menulis ilmuwan Muslim Nusantara. Dahlan (2018) menulis artikel tentang tradisi intelektual ulama Sumatera Timur, namun belum secara menyeluruh mengkaji tradisi ilmiah ulama Nusantara melainkan secara parsial membahas tradisi intelektual ulama Sumatera Timur semata.…”
Section: Pendahuluanunclassified